Oxford international lower seconadary english student book 1 for grade 6 - Barber, Alison (Karachi: Oxford University Press., 2022)
The Oxford International Lower Secondary English: Student Book 1 for Grade 6 introduces students to a more advanced study of English language and literature. It builds on foundational skills in reading, writing, and comprehension, while encouraging deeper analysis of texts, including fiction, non-fiction, and poetry. The book helps students develop critical thinking and effective communication through structured lessons on grammar, punctuation, vocabulary, and writing techniques such as persuasive and narrative writing. With a global approach to content, the book aims to foster a broad understanding of different cultures and perspectives, preparing students for higher levels of English learning.